The Impact of Maternal Health Conditions On the Risk of HIE in Newborns - Sana; Atiq Ur Rahman; Khan, Sher Alam; Tabassum, Rabia; Ismail; Sajid, Irum (Indus Journal of Bioscience Research, 2025)
The aim to determine how maternal disorders may impact hypoxic-ischemic encephalopathy (HIE) in the newborn, a severe neonatal condition that is defined by inadequate oxygen supply and brain damage. The findings of this present study were based on data collected from 1,200 pregnancies to determine how factors like hypertension, diabetes mellitus and infections that occur intrauterine affect the risk and severity of HIE. The study was conducted at Pediatrics Department, Ayub Teaching Hospital, and Abbottabad. The study shows that hypertensive disorders were the significant risk factors for HIE as compared to the other diseases (RR = 2.4, p < 0.01), intrauterine infections (RR = 2.1,p< 0.01) and diabetes mellitus (RR = 1.8, p < 0.05). On the other hand, emergency caesarean sections were associated with a threefold increased risk of HIE, which is commensurate with the severity of high-risk deliveries. Neonates who had exposure to multiple maternal conditions confirmed even higher risk of severe HIE, 72 % of such babies (p < 0.01). That can be explained by the fact that the outcomes obtained reflect prior similar research and contribute new knowledge on the impact of the aggregation of those conditions. The study raises the issue of the need for a coordinated system of prenatal care and early identification of the problem combined with such recommendations to reduce the risk of developing HIE and enhance the baby’s condition. The main recommendation put forward would be proper maternal health management especially learnt with complications in pregnancy to help reduce this major cause of neonatal morbidity and mortality.